2020
DOI: 10.1359/jbmr.080808
|View full text |Cite
|
Sign up to set email alerts
|

Postpubertal Architectural Developmental Patterns Differ Between the L3 Vertebra and Proximal Tibia in Three Inbred Strains of Mice

Abstract: An understanding of normal microarchitectural bone development patterns of common murine models is needed. Longitudinal, structural, and mineralization trends were evaluated by in vivo CT over 12 time points from 6-48 wk of age at the vertebra and tibia of C3H/HeN, C57BL/6, and BALB/C mice. Longitudinal growth occurred rapidly until 8-10 wk, slowed as the growth plate bridged, and fused at 8-10 mo. Structural augmentation occurred through formation of trabeculae at the growth plate and thickening of existing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 63 publications
11
83
4
Order By: Relevance
“…Mice received a dose of 640 mGy per scan, leading to a total dose of 3.8 Gy (the scan at the last time point has no influence). This dose is higher than doses that have been reported previously to have no effect on the bone microstructure in C57Bl/6 mice [19,30] or rats [47]. In a study where rats were scanned at nine time points, however, the dose was higher; but still no negative effect of radiation was found in the bone microstructure [48].…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Mice received a dose of 640 mGy per scan, leading to a total dose of 3.8 Gy (the scan at the last time point has no influence). This dose is higher than doses that have been reported previously to have no effect on the bone microstructure in C57Bl/6 mice [19,30] or rats [47]. In a study where rats were scanned at nine time points, however, the dose was higher; but still no negative effect of radiation was found in the bone microstructure [48].…”
Section: Discussionmentioning
confidence: 65%
“…In the same study it was found that BV/TV in the fifth lumbar vertebra increased between the ages of 2 and 12 months [41]. In contrast, Buie et al [30] reported stable BV/TV in C57Bl/6 J mice in the third lumbar vertebra between the ages of 3 and 7 months, and Glatt et al [42] found a decline in BV/TV in female C57Bl/6 J mice from 2 months old on in the fifth lumbar vertebra. In general, declines in the long bones have been observed from an early age on [41][42][43][44].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Contradicting results may be due to the age of the animals at OVX (previous studies using no less than 3-month-old C57BL/6J mice) and the duration of time elapsed following OVX (8 weeks). The various skeletal alterations during the 2-4 months old period caused by differing post-pubertal architectural development patterns among different strains may account for discrepancies arising from the different starting ages (25). It would be interesting to Table V. Effect of estrogen deprivation on body weight, bone mass and microarchitecture in three inbred and outbred mice.…”
Section: -Week-old ------------------------------------------------mentioning
confidence: 99%